On-demand expansion fluorescence and photoacoustic microscopy (ExFLPAM) - Xuan Mu; Chenshuo Ma; Xuan Mei; Junlong Liao; Rebecca Bojar; Sizhe Kuang; Qiangzhou Rong; Junjie Yao; Yu Shrike Zhang (Photoacoustics, 2024)
Expansion microscopy (ExM) is a promising technology that enables nanoscale imaging on conventional optical microscopes by physically magnifying the specimens. Here, we report the development of a strategy that enables i) on-demand labeling of subcellular organelles in live cells for ExM through transfection of fluorescent proteins that are well-retained during the expansion procedure; and ii) non-fluorescent chromogenic color-development towards efficient bright-field and photoacoustic imaging in both planar and volumetric formats, which is applicable to both cultured cells and biological tissues. Compared to the conventional ExM methods, our strategy provides an expanded toolkit, which we term as expansion fluorescence and photoacoustic microscopy (ExFLPAM), by allowing on-demand fluorescent protein labeling of cultured cells, as well as non-fluorescent absorption contrast-imaging of biological samples.